Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Section: 1 volume (unpaged) : chiefly illustrations (some color) ; 26 cm
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

« Des femmes et de la territorialité » Début d’un dialogue sur la nature sexuée des droits des autochtones - Woudenberg, Gerdine Van; Lapierre, Christine (Recherches amérindiennes au Québec, 2004)
Cet article, qui se situe dans l’ensemble des discours sur les droits des autochtones, explore de façon spécifique le sujet du rapport des femmes à la territorialité. En utilisant comme étude de cas les cultures wabanakies de la côte Est, l’auteure réexamine de manière critique les documents historiques pour analyser le rapport des femmes au « lieu » à travers leur relation à leur environnement et elle étudie comment le contexte de cette relation a été transformé par les processus de colonisation. Puisque ce texte s’insère dans le large champ des discours sur les droits autochtones, il soulève des questions importantes sur la position des femmes autochtones dans les processus actuels de reconnaissance des droits et des titres, non seulement comme participantes actuelles mais aussi comme acteurs historiques.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; environnement; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; territoire; thématiques; wabanakie

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme